Microbial community shifts during salt mitigation treatments of historic buildings using mineral poultices: a long-term monitoring of salt and associated biofilms - Tichy, Johannes; Sipek, Beate; Ortbauer, Martin; Fürnwein, Lukas; Waldherr, Monika; Graf, Alexandra; Sterflinger, Katja; Piñar, Guadalupe (Frontiers in Microbiology, 2025)
Increased heavy rainfall followed by periods of drought due to climate change is leading to more frequent salt-crystallization cycles. This not only leads to increased salt-weathering on architectural surfaces of cultural heritage monuments, but also creates an ideal ecological niche for the formation of biofilms by salt-loving microorganisms. These biofilms, characterized by a distinctive pink coloration, cause additional esthetic alterations to affected surfaces. In this study, mineral poultices prepared with different clay minerals (sepiolite, kaolinite and vermiculite) were developed and tested for a long-term (1 year) application on salt-weathered surfaces, thus contributing to their preservation. The poultices were tested on the surfaces of two historic buildings: the St. Virgil’s Chapel in Vienna and the Mauerbach Charterhouse in Lower Austria, both showing salt efflorescence and a uniform pink biofilm. First, the poultices were tested to evaluate their salt retention capacity, salt-weathering resistance and processability. The retention properties of the poultices were examined by measuring their salt content throughout the treatment using high performance liquid chromatography (HPLC) and continuous flow analysis (CFA). Salt content was also measured on the wall surfaces before and after treatment. Second, the effect of the desalination treatments on salt-associated pink biofilms was also evaluated. The shifts within the biofilm communities during and after the treatment were monitored by qPCR and long-read archaeal- and bacterial-16S rRNA amplicon analysis using the Nanopore sequencing technology. The results demonstrate that both the selected clay minerals and the salt composition in the treated areas significantly influenced the salt storage capacity of the poultices and their resistance to salt weathering. Fluctuations in salt load and ionic composition during and after treatment affected biofilm composition, with bacterial communities proving more sensitive than archaea to these changes. Both qPCR and metataxonomic results show that the effects of the poultices on the colonizing biofilms depend not only on the composition of their microbial members, but also on external abiotic factors such as the chemical composition and concentration of the salt mixtures on the surfaces. In addition, the biodiversity within the biofilms shows to be affected differently depending on the mineral clay used.